Optimization of a Mixed Refrigerant Based H2 Liquefaction Pre-Cooling Process and Estimate of Liquefaction Performance with Varying Ambient Temperature - Steven Jackson; Eivind Brodal (Energies, 2021)
Hydrogen used as an energy carrier can provide an important route to the decarbonization of energy supplies, but realizing this opportunity will require both significantly increased production and transportation capacity. One route to increased transportation capacity is the shipping of liquid hydrogen, but this requires an energy-intensive liquefaction step. Recent study work has shown that the energy required in this process can be reduced through the implementation of new and improved process designs, but since all low-temperature processes are affected by the available heat-sink temperature, local ambient conditions will also have an impact. The objective of this work is to identify how the energy consumption associated with hydrogen liquefaction varies with heat-sink temperature through the optimization of design parameters for a next-generation mixed refrigerant based hydrogen liquefaction process. The results show that energy consumption increases by around 20% across the cooling temperature range 5 to 50 °C. Considering just the range 20 to 30 °C, there is a 5% increase, illustrating the significant impact ambient temperature can have on energy consumption. The implications of this work are that the modelling of different liquified hydrogen based energy supply chains should take the impact of ambient temperature into account.